UV‐resistant yeasts isolated from a high‐altitude volcanic area on the Atacama Desert as eukaryotic models for astrobiology. Issue 4 (4th July 2015) - Pulschen, André A.; Rodrigues, Fabio; Duarte, Rubens T. D.; Araujo, Gabriel G.; Santiago, Iara F.; Paulino‐Lima, Ivan G.; Rosa, Carlos A.; Kato, Massuo J.; Pellizari, Vivian H.; Galante, Douglas
Abstract The Sairecabur volcano (5971 m), in the Atacama Desert, is a high‐altitude extreme environment with high daily temperature variations, acidic soils, intense UV radiation, and low availability of water. Four different species of yeasts were isolated from this region using oligotrophic media, identified and characterized for their tolerance to extreme conditions. rRNA sequencing revealed high identity (>98%) to Cryptococcus friedmannii, Exophiala sp., Holtermanniella watticus, and Rhodosporidium toruloides. To our knowledge, this is the first report of these yeasts in the Atacama Desert. All isolates showed high resistance to UV‐C, UV‐B and environmental‐UV radiation, capacity to grow at moderate saline media (0.75–2.25 mol/L NaCl) and at moderate to cold temperatures, being C. friedmannii and H. watticus able to grow in temperatures down to −6.5°C. The presence of pigments, analyzed by Raman spectroscopy, correlated with UV resistance in some cases, but there is evidence that, on the natural environment, other molecular mechanisms may be as important as pigmentation, which has implications for the search of spectroscopic biosignatures on planetary surfaces. Due to the extreme tolerances of the isolated yeasts, these organisms represent interesting eukaryotic models for astrobiological purposes.